Intercultural Communicative Competence in English Language Teaching: Towards Validation of Student Identity - Galante, Angelica (BELT - Brazilian English Language Teaching Journal, 2015)
Many English programs in Brazil, and in other countries, focus on teaching linguistic items and neglect the fact that culture and language are tightly linked. Cultural dimensions are, even if implicitly, prevalent in textbooks, teacher discourse, and the media. However, cultural references in English Language Teaching (ELT) are often regarded as being American or British, disregarding the culture of speakers of English from many other countries, including Brazil. As well, ELT in the 21st century has evolved and the concept of communicative competence does not rely on language only; it also includes intercultural awareness. Another integral element in ELT that goes beyond language learning is the representation of one’s identity. In this sense, implementing intercultural communicative competence (ICC) in ELT allows learners to express their identities while engaging in meaningful discussions about cultural views.